Therapeutic Potential of HUMSCs in Female Reproductive Aging - Mei, Qiaojuan; Mou, Hongbei; Liu, Xuemei; Xiang, Wenpei (Frontiers in Cell and Developmental Biology, 2021)
With the development of regenerative medicine, stem cells are being considered more frequently for the treatment of reproductive aging. Human umbilical cord mesenchymal stem cells have been reported to improve the reserve function of aging ovaries through their homing and paracrine effects. In this process, paracrine factors secreted by stem cells play an important role in ovarian recovery. Although the transplantation of human umbilical cord mesenchymal stem cells to improve ovarian function has been studied with great success in animal models of reproductive aging, their application in clinical research and therapy is still relatively rare. Therefore, this paper reviews the role of human umbilical cord mesenchymal stem cells in the treatment of reproductive aging and their related mechanisms, and it does so in order to provide a theoretical basis for further research and clinical treatment.